If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -2) = -6 + 12x Reorder the terms: 3(-2 + 4x) = -6 + 12x (-2 * 3 + 4x * 3) = -6 + 12x (-6 + 12x) = -6 + 12x Add '6' to each side of the equation. -6 + 6 + 12x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 0 + 12x = -6 + 6 + 12x 12x = -6 + 6 + 12x Combine like terms: -6 + 6 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 15+18x=19.50 | | 55+10x=20+15x | | 2x+3y+10=180 | | 8+x*4=4 | | x^2+y^2+6x-14y-12=0 | | (y-4)=7(2y+1) | | -2(x-1)=24 | | 8x+9=5x+42 | | 8x+60=4x+88 | | 49p^2-16=0 | | 20=b-7 | | 3b-23+b=33-38b+3 | | 5k^2+5k+3= | | ln(x^2)-ln(x+2)=0 | | 6+2h=24 | | -52=8+-5n | | 5k^2+5k-3= | | 4e-18=-10 | | 5x^2-2-12=0 | | -2n+3=33 | | 2x+4=n | | 17m+12=-6m^2 | | 40w+60=500 | | 20L-K=180 | | (5x+7)-(2x-3)= | | -28+7x+x^2=0 | | 4x-25=26-13x | | 5(3x-7)=7(2x-5) | | 2(5k-7)-3= | | 3(21-7x)=-42 | | 8+3(4n-3)=-49 | | -6(n+5)=-30 |